Enhancing Thai EFL Students’ Speaking Skills through Project-Based Learning Assisted by Flashcards - Indiani, Evi; Erlindawaty, Erlindawaty (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aimed to investigate the effectiveness of project-based learning assisted by flashcards in enhancing Thai EFL students' speaking skills. The study was conducted at Koksai Anusorn School, Satun, Thailand, and involveed 30 fifth-grade students divided into experimental and control groups. The experimental group was taught using project-based learning assisted flashcards, while the control group received conventional instruction using English textbook. The study approach used was quantitative with a quasi-experimental design in the form of a pretest and posttest experimental and control groups. Data were collected through speaking performance tests covering five aspects: fluency, grammar, vocabulary, pronunciation, and comprehension. The data were analyzed using descriptive statistics, Shapiro-Wilk normality tests, and paired samples t-tests with the help of SPSS software. The results showed that the mean score of the experimental group increased from 67.67 to 91.00, while the control group enhanced from 67.00 to 85.00. The paired samples t-test revealed a significant difference in both groups (p = 0.000), but the experimental group showed a greater mean gain of 23.33 points compared to 18.00 points in the control group. The Shapiro-Wilk test confirmed that all data were normally distributed, making parametric analysis appropriate. These findings indicate that project-based learning assisted by flashcards can significantly enhance Thai EFL students’ speaking skills.